Analisis Penerapan Pembelajaran Bilingual Siswa Kelas IV di SDI Rutosoro - Una, Luxcya Martir Wona; Yuliana Beku, Veronika; Noge, Maria Desidaria (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Bilingual learning is bilingual learning, in which Indonesian and foreign languages are combined with each other. Objectives: The main purpose of this study is to analyze the application of Bilingual learning at SDI Rutosoro, as a provision to help students master the two languages taught in an academic context, in addition to practicing language and communication skills, and to develop foreign languages. The research approach used is a qualitative approach with a descriptive method. Methods: The data collection method in this study uses interviews, observations and documentation. Results: Based on the results of the research in the implementation of bilingual learning, the main is preparation in carrying out learning activities that refer to the applicable curriculum as well as infrastructure and support from the school, in the process of implementing bilingual learning carried out at SDI Rutosoro. Conclusion: The results of the analysis showed that there was student activity in participating in bilingual learning which was shown by an activity percentage of 65%. Keywords: Bilingual Learning, Primary School